Iranian Dietary Patterns and Risk of Colorectal Cancer - Hosein Azizi; Khairollah Asadollahi; Elham Davtalab Esmaeili; Mohammad Mirzapoor (Tabriz University of Medical Sciences, 2015)
Background: Role of diet on colorectal cancer (CRC) has been considered in terms of single foods and nutrients, but less frequently in terms of dietary patterns in Iran. The objective of this study was to determine the association between Iranian dietary patterns and CRC.Methods: This case-control study was conducted in four hospitals in Tabriz City of Iran including 414 participants aged 35-75 years:207 cases with CRC confirmed by pathology and colonoscopy findings were selected and 207 controls free of neoplastic conditions and diet-related chronic diseases (from the same hospital at the same period for the cases). Dietary data were assessed using a 123-item semi-quantitative food frequency questionnaire. Two dietary patterns were found by using of Principal Component Analysis (PCA) method;"Healthy pattern"and "Iranian pattern". Multivariate logistic regression analysis was used to estimate adjusted odds ratios (OR) for relationship between dietary patterns and colorectal cancer.Results: After adjusting for confounding factors, the Iranian dietary pattern was significantly associated with an increased odds of colorectal cancer (OR= 1.46; 95% Confidenec Interval (CI)=1.05-2.19) while a reduced odds of colorectal cancer was observed with the Healthy dietary pattern (OR=0.18; 95% CI= 0.091-0.47).Conclusion: Iranian dietary pattern (IDP) seems to increase the odds of colorectal cancer and protective effect of Healthy dietary pattern.